ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS UNTUK MENLAI KINERJA KEUAGAN PADA PT. BANK CIMB NIAGA TBK - Bella, VIOLA; Oktafia, Renny (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
The existence of a condition of speed in the economy of a nation is of course instigated by its economic action in the nation itself. The whole action is a cog for economic action bang role is important for the country. Bentala banking is an institution that is highly positioned in the field of the economy of a nation. In this study, it uses a descriptive method with a quantitative approach, namely processing with real data, after which it is calculated, compared, and described the results of these calculations, the financial statements of PT. Bank CIMB Niaga Tbk. One of the growing banking financial institutions is Bank CIMB Niaga. PT Bank CIMB Niaga is a private bank subsidiary of CIMB and is a company providing financial services. CIMB Niaga was formed on 26 September 1955 nicknamed Bank Niaga. Its purpose is to develop core scores and expertise in the banking sector. As a result, Bank Niaga has become a distributor of quality products and services that are recommended. Bank CIMB Niaga received three awards at the 2022 Asian Banking and Finance (ABF) Corporate & Investment Banking Awards. Therefore, it is necessary to implement good banking management and be accommodated by resources.